Human Liver Organoid Models for Assessment of Drug Toxicity at the Preclinical Stage - Karabicici, Mustafa; Akbari, Soheil; Ertem, Ozge; Gumustekin, Mukaddes; Erdal, Esra (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
The hepatotoxicity of drugs is one of the leading causes of drug withdrawal from the pharmaceutical market and high drug attrition rates. Currently, the commonly used hepatocyte models include conventional hepatic cell lines and animal models, which cannot mimic human drug-induced liver injury (DILI) due to poorly defined dose-response relationships and/or lack of human-specific mechanisms of toxicity. In comparison to 2D culture systems from different cell sources such as primary human hepatocytes and hepatomas, 3D organoids derived from an inducible pluripotent stem cell (iPSC) or adult stem cells are promising accurate models to mimic organ behavior with a higher level of complexity and functionality owing to their ability to self-renewal. Meanwhile, the heterogeneous cell composition of the organoids enables metabolic and functional zonation of hepatic lobule important in drug detoxification and has the ability to mimic idiosyncratic DILI as well. Organoids having higher drug-metabolizing enzyme capacities can culture long-term and be combined with microfluidic-based technologies such as organ-on-chips for a more precise representation of human susceptibility to drug response in a high-throughput manner. However, there are numerous limitations to be considered about this technology, such as enough maturation, differences between protocols and high cost. Herein, we first reviewed the current preclinical DILI assessment tools and looked at the organoid technology with respect to in vitro detoxification capacities. Then we discussed the clinically applicable DILI assessment markers and the importance of liver zonation in the next generation organoid- based DILI models.
Keywords: Drug metabolism